Fabrication and optimization of camptothecin loaded Eudragit S 100 nanoparticles by Taguchi L4 orthogonal array design - Mahalingam, Manikandan (Int J Pharm Investig, 2015)
INTRODUCTION: The objective of this investigation was to design and optimize the experimental conditions for the fabrication of camptothecin (CPT) loaded Eudragit S 100. Nanoparticles, and to understand the effect of various process parameters on the average particles size, particle size uniformity and surface area of the prepared polymeric nanoparticles using Taguchi design. MATERIALS AND METHODS: CPT loaded Eudragit S 100 nanoparticles were prepared by nanoprecipitation method and characterized by particles size analyzer. Taguchi orthogonal array design was implemented to study the influence of seven independent variables on three dependent variables. Eight experimental trials involving seven independent variables at higher and lower levels were generated by design expert. RESULTS: Factorial design result has shown that (a) except, β-cyclodextrin concentration all other parameters do not significantly influenced the average particle size (R1); (b) except, sonication duration and aqueous phase volume, all other process parameters significantly influence the particle size uniformity; (c) all the process parameters does not significantly influence the surface area. CONCLUSION: The R1, particle size uniformity and surface area of the prepared drug-loaded polymeric nanoparticles were found to be 120 nm, 0.237 and 55.7 m(2) /g and the results were good correlated with the data generated by the Taguchi design method.